(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
This essay describes some aspects of the cinematographic object understood not only as an artistic product to be evaluated, nor only in its narrative content, but as the center of a composite device. Such a device combines different elements: the film in its entirety, the author’s thoughts, and the fundamental experience of the viewer. Following Christian Metz’s perspective, the first result we may findis the recognition of a fundamental duality of the film: compared to other means of expression, the film stimulates many axes of perception while being at the same time less perceptual, because what is shown on the screen is always recorded, past and basically absent. This duplicity of cinema is connected to other issues psychoanalytic perspective offers convincing answers to: the ’paradox’ of fiction; the spectator’s identification with his own eyes; the doubling of the distance from the cinematic images.